2022
DOI: 10.3390/cancers14092325
|View full text |Cite
|
Sign up to set email alerts
|

A Data Science Approach for the Identification of Molecular Signatures of Aggressive Cancers

Abstract: The main hallmarks of cancer include sustaining proliferative signaling and resisting cell death. We analyzed the genes of the WNT pathway and seven cross-linked pathways that may explain the differences in aggressiveness among cancer types. We divided six cancer types (liver, lung, stomach, kidney, prostate, and thyroid) into classes of high (H) and low (L) aggressiveness considering the TCGA data, and their correlations between Shannon entropy and 5-year overall survival (OS). Then, we used principal compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 143 publications
0
4
0
Order By: Relevance
“…CLEC11A (C‐type lectin domain family 11 member A), also known as osteolectin or stem cell growth factor‐β, can promote bone formation through stimulating the differentiation of mesenchymal progenitor cells into osteoblasts 60 and maintain the adult skeleton age‐related bone loss and fracture repair 61 . CLEC11A could recruit the endothelial cells in lung cancer 62 and neutralization of CLEC11A reduced metastasis and viability of cancer stem cells in hepatocellular carcinoma 63 . A recent study performed by Sun et al 64 .…”
Section: Discussionmentioning
confidence: 99%
“…CLEC11A (C‐type lectin domain family 11 member A), also known as osteolectin or stem cell growth factor‐β, can promote bone formation through stimulating the differentiation of mesenchymal progenitor cells into osteoblasts 60 and maintain the adult skeleton age‐related bone loss and fracture repair 61 . CLEC11A could recruit the endothelial cells in lung cancer 62 and neutralization of CLEC11A reduced metastasis and viability of cancer stem cells in hepatocellular carcinoma 63 . A recent study performed by Sun et al 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Although this discrepancy may seem strange, it is because the PCA algorithm identifies the genes that best explain the variance between the H and L classes, while the RFC algorithm maximizes the classification power of a given tumor as belonging to either the H or L class. Additionally, when we mapped the genes listed by both PCA and RFC onto the interactome, we found that they were all close neighbors [23].…”
Section: Markers Of Aggressivenessmentioning
confidence: 96%
“…It is caused by the disruption of various pathways, including those involved in growth factor signaling, developmental pathways, such as WNT, Hedgehog, Notch, and Hippo, and other mechanisms, such as mTOR and NF-κB signaling that affect cell growth and proliferation [22]. Additionally, the interplay among these pathways in cancer must be considered [23]. For example, some tumors display interactions between the WNT pathway and other important ones, such as EGF, FGF, Hedgehog, mTOR, Notch, TGF-β, and NF-κB [24].…”
Section: Markers Of Aggressivenessmentioning
confidence: 99%
“…The method of evaluating the expression of genes by reference to the population of DEGs has been used to identify up-regulated hub targets in solid tumors [10,11,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%